DYNAMICS OF MENTAL WORKING CAPACITY DURING THE PROFESSIONAL ACTIVITY OF TEACHERS - Латина, Анна (SWorldJournal, 2021)
The paper examines the assessment of the dynamics of the mental working capacity of teachers of institutions of general secondary education during their work. 51 teachers were examined. Features of the dynamics of mental working capacity reflect age patt